2023
DOI: 10.1007/s00467-023-05888-z
|View full text |Cite
|
Sign up to set email alerts
|

Urine biomarker score captures response to induction therapy with lupus nephritis

Abstract: Background The Renal Activity Index for Lupus (RAIL) consists of urine protein assessment of neutrophil gelatinase–associated lipocalin, kidney injury molecule-1, monocyte chemotactic protein 1, adiponectin, hemopexin, and ceruloplasmin, which non-invasively identifies lupus nephritis (LN). We aimed to delineate RAIL scores with inactive versus active LN and changes over time with response to LN induction therapy. Methods There were 128 pediatric patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…These findings align with previous works ( 15 17 , 21 ). However, a detailed comparative analysis of follow-up test results is lacking, with only one study reporting that an HPX-inclusive biomarker score could represent the response to induction therapy in patients with LN ( 34 ). Our study revealed a positive correlation between changes in biomarker levels and SLEDAI-2k scores, suggesting a highly promising outcome.…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with previous works ( 15 17 , 21 ). However, a detailed comparative analysis of follow-up test results is lacking, with only one study reporting that an HPX-inclusive biomarker score could represent the response to induction therapy in patients with LN ( 34 ). Our study revealed a positive correlation between changes in biomarker levels and SLEDAI-2k scores, suggesting a highly promising outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of LN should be viewed as a longlasting battle, and patients should be informed upfront about the benefit of maintaining treatment for several years, while of course, accounting for their preferences and needs. We anticipate that intensive research in the field of biomarkers, including plasma [69] and urine [70][71][72][73][74][75][76][77] mediators such as TWEAK, VCAM-1, CD163, and matrix metalloproteinases, will be fruitful and provide novel non-invasive tools to monitor renal disease activity, thus enabling prognostication and treatment tailoring in patients with LN.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, the RAIL biomarkers could accurately predict response to therapy and propensity towards relapse, highlighting that these biomarkers not only hold diagnostic potential but are also capable of predicting the prognosis. RAIL scores could also distinguish clinically active LN from inactive LN or healthy controls in pediatric patients with SLE and decreased by ≥1 point in patients with complete remission [94]. Importantly, the RAIL score outperformed the rSLEDAI in capturing high LN activity (AUC of 0.79 vs. 0.62, respectively).…”
Section: Rail Scorementioning
confidence: 94%
“…Importantly, the RAIL score outperformed the rSLEDAI in capturing high LN activity (AUC of 0.79 vs. 0.62, respectively). Furthermore, the RAIL score could reveal subclinical/lowmoderate LN activity in patients with an rSLEDAI of 0 who had a kidney biopsy more than 3 months ago [95], underscoring its potential as a method to routinely monitor subclinical kidney disease [94].…”
Section: Rail Scorementioning
confidence: 99%